Organic products based on chromium for poultry production. Main advances in the last years - Valera, M.; Gutiérrez, Odilia; Elías, A. (Cuban Journal of Agricultural Science, 2019)
This study reviews the progress of recent years in the use of organic chromium products in poultry feed and production. Important topics such as the functions of this mineral element, the most used types of products, their supplementation levels, as well as the effects of the inclusion of this microelement in the diets through different forms, in the productive performance of animals, mitigation of caloric stress and other indicators of interest were analyzed. The most promising, according to the obtained effects, are chromium picolinate and chromium linked to yeast, and the respective responses of animals to their supplementation have been the main focus of research in recent years. Keywords: supplementation, chromium, broilers, glucose